Effect of Different Surface Treatments on Microtensile Bond Strength of Composite Resin to Normal and Fluorotic Enamel after Microabrasion - Mahshid Mohammadi Basir; Mohammad Bagher Rezvani; Elham Tabatabai Ghomsheh; Zahra Malek Hosseini (Tehran University of Medical Sciences, 2017)
Objectives: This study aimed to determine the effect of surface treatments such as tooth reduction and extending the etching time on microtensile bond strength (µTBS) of composite resin to normal and fluorotic enamel after microabrasion. Materials and Methods: Fifty non-carious anterior teeth were classified into two groups of normal and fluorotic (n=25) using Thylstrup and Fejerskov index (TFI=4-6). Teeth in each group were treated with five modalities as follows and restored with OptiBond FL and Z350 composite resin: 1-Etching (30 seconds), bonding, filling (B); 2-Tooth reduction (0.3mm), etching, bonding, filling (R-B); 3-Microabrasion (120 seconds), etching, bonding, filling (M-B); 4- Microabrasion, tooth reduction, etching, bonding, filling (M-R-B); and 5- Microabrasion, etching (60 seconds), bonding, filling (M-2E-B). Ten experimental groups (n=5) were designed; 150 rectangular samples (10 in each group) with a cross-sectional area of 1×1mm2 were prepared for µTBS test. Failure mode was determined under a stereomicroscope and one specimen was selected from each group for scanning electron microscopy (SEM) analysis. Data were analyzed using two-way ANOVA and Tukey's test. Results: The µTBS to normal enamel was higher than to fluorotic enamel in all groups except for group (R-B). The Maximum and minimum µTBS were noted in the group (normal, reduction, bonding) and (fluorosed, microabrasion, bonding), respectively.  Tooth reduction increased µTBS more effectively than extended etching time after microabrasion. Conclusions: Fluorosis may reduce µTBS of composite resin to enamel. Microabrasion reduced the bond strength. Tooth reduction and extended etching time increased µTBS of composite resin to both normal and fluorotic enamel.